Differences in nutritional quality between wild and domesticated forms of barley and emmer wheat. (March 2017) - Hebelstrup, Kim Henrik
Highlights: Wild and domesticated grains have very different nutritional qualities. We hypothesize that domestication increased the glycemic index of grains. The glycemic index may have played a role for the evolution of grains. Abstract: Grasses such as wheat and barley constitute some of the main crops currently cultivated worldwide. Cultivation of wild cereals such as Hordeum spontaneum (wild barley) and Triticum diccocoides (wild emmer) started in southwest Asia. Despite the many studies on the origins of agriculture and plant domestication, surprisingly few studies have discussed the importance of the nutritional quality of barley and emmer wheat in their evolution. A comparison of domesticated forms of these cereals with their wild progenitors suggests an evolution towards bigger grains with higher glycemic loads in the form of higher relative starch content with lower relative protein, fiber and mineral contents. In this work we hypothesize that in addition to the simple explanation that larger grains emerged under domestication, complex and indirect effects such as increased glycemic index and sweet taste should also be taken into consideration.